Evolutionary science in denominational colleges at Australian universities, 1907–2020. - Barnes, Joel (Paedagogica Historica, 2024)
This article examines the place of evolutionary science in protestant and Catholic residential colleges associated with Australian public universities across the twentieth and early twenty-first centuries. Although faith-based universities are a relatively recent phenomenon in Australia, a quasi-federal model of secular teaching and accrediting universities linked to church-run non-teaching residential colleges developed with the founding of the first Australian university, the University of Sydney, in the 1850s. The model was subsequently replicated, with local variations, across the first generation of Australian public universities. This interface between mainstream secular and more selective religious spaces makes the colleges an instructive setting in which to examine science-and-religion ideas in institutional context. As principally pastoral, residential institutions the colleges did not have curricula or significant research programmes of their own, but student publications produced within them shed light on the attitudes and beliefs of students and some staff regarding evolutionary science, and science more generally, in relation to religion. The article analyses a corpus of more than 700 student publications published between 1907 and 2020 and associated with the Universities of Sydney, Melbourne and Queensland, the three institutions with the most developed collegiate systems. The analysis shows the complexity of ways in which evolutionary science was understood within the denominational colleges, and the limits set to those understandings by college authors' plural institutional contexts.